2013
DOI: 10.1371/journal.pgen.1003449
|View full text |Cite
|
Sign up to set email alerts
|

All SNPs Are Not Created Equal: Genome-Wide Association Studies Reveal a Consistent Pattern of Enrichment among Functionally Annotated SNPs

Abstract: Recent results indicate that genome-wide association studies (GWAS) have the potential to explain much of the heritability of common complex phenotypes, but methods are lacking to reliably identify the remaining associated single nucleotide polymorphisms (SNPs). We applied stratified False Discovery Rate (sFDR) methods to leverage genic enrichment in GWAS summary statistics data to uncover new loci likely to replicate in independent samples. Specifically, we use linkage disequilibrium-weighted annotations for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
368
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 281 publications
(389 citation statements)
references
References 46 publications
21
368
0
Order By: Relevance
“…We thus examined if these evolutionary DMRs are enriched for association with schizophrenia or other human traits. Using previously published methodologies (18,29,30) and publicly available GWAS datasets we systematically analyzed twelve diverse phenotypes to investigate the potential role of regions susceptible to epigenetic variation in the emergence of specific traits in the human lineage.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
See 3 more Smart Citations
“…We thus examined if these evolutionary DMRs are enriched for association with schizophrenia or other human traits. Using previously published methodologies (18,29,30) and publicly available GWAS datasets we systematically analyzed twelve diverse phenotypes to investigate the potential role of regions susceptible to epigenetic variation in the emergence of specific traits in the human lineage.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…2, 2017; negative log 10 of a normal distribution. Leftwards deflections from the null line represent enrichment (29).…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
See 2 more Smart Citations
“…In this type of analysis, the researcher examines the most strongly associated SNPs in a GWAS and tests whether they fall disproportionately in specific types of genomic regions. These studies have found, for example, that SNPs identified in GWASs are enriched in protein-coding exons, in promoters, in UTRs, 2,4 and among those that influence gene expression. 5,6 Further, in some cases, SNPs associated with a trait are enriched in gene regulatory regions in specific cell types [7][8][9][10][11][12][13][14][15][16][17][18] or near genes expressed in specific cell types.…”
Section: Introductionmentioning
confidence: 99%